Análise das matérias de saúde bucal veiculadas na mídia impressa no Espírito Santo, nos anos de 2004 a 2009 - Cavaca, Aline Guio (2011)
This dissertation is presented in the form of articles. The work presented in this study analyzed the oral health materials broadcast in print media in Espírito Santo, in the years 2004-2009. The first paper is a quantitative study that aims to delineate the main characteristics of the materials on oral health broadcast in print media of Espírito Santo from 2004 to 2009, in order to analyse and compare the issues, approaches and journalistic relevant related to the thematic priority in the newspapers A Tribuna e A Gazeta. The second article is a qualitative study that aims to understand how the informations about oral health are broadcast on press media in ES, to examine if the power of media is exploiting a critical education, health promotion and consumerism in oral health. The first study found that issues discussed included from information about oral health policies, community service and prevention of oral health diseases, to the “aesthetic tendencies” of smile, the dissemination of new technologies and dental specialities; there was a predominance of even-numbered pages, fewer calls in the first page and broadcast in full-page, which means a moderate appreciation of these issues; different editorial projects, plus the difference in audience determined the journalistic standart and predominated source specialist. Despite the oral health news not shows “scoops”, they can be worked through a conscious journalism practice, in order to evoke the extraordinary from ordinary, giving rise to news of social relevance in both newspapers. The second article conducted a content analysis of empirical data, resulting in nine analytical categories: accountability of the individual, extreme conditions, access to public / private services, popular imagination of the dentist and dental office, pathologizing of halitosis, aesthetic value, determinants of oral health, hygiene and nutrition habits and prevention. It was concluded that the media approach of oral health cuts across a complex of social, cultural, political, biological and economic factors, which highlights the importance of communication in context with the interests of society, interactive and dialogue, which explore their critical power in education and health promotion, and relays a conscious consumerism in oral health.